Association of oestrogen receptor gene polymorphisms with age at onset of rheumatoid arthritis. Issue 1 (1st January 1999) - Ushiyama, Toshio; Mori, Kanji; Inoue, Koji; Huang, Jie; Nishioka, Junichi; Hukuda, Sinsuke
Abstract : OBJECTIVE: In view of the possible role of oestrogens in the pathogenesis of rheumatoid arthritis (RA), this study investigated the association between oestrogen receptor (OR) gene polymorphisms and RA. METHODS: Pvu II and Xba I restriction fragment length polymorphisms of the OR gene were analysed in 70 male and 240 female patients with RA, and in 300 male and 350 female controls. The absence or presence of restriction sites were represented as P, p (Pvu II ) or X, x (Xba I ). The distribution of OR genotypes was compared between the RA and control subjects by sex. RA patients were divided into subgroups according to their OR genotypes, then the age at onset, seropositivity, and rheumatoid nodule positivity were compared between the subgroups. RESULTS: The OR genotype frequency of distribution did not have significant differences between the male RA and male controls nor between the female RA and female controls. In women with RA, there was a significant difference of age at onset between the subgroups (uncorrected p=0.047, corrected p=0.94). Female patients with the OR genotype PPxx (homozygote of Px) tended to have developed RA at a younger age, whereas those with PPXX and ppxx (lack of Px haplotype) developed RA at an older age. In men with RA, there was no association between the OR genotype and age at onset. In seropositivity and rheumatoid nodule positivity, there was no significant difference between subgroups for either sex. CONCLUSIONS: Some variants of the OR gene are related to the onset of RA in women in certain age periods, suggesting the role of the interaction between the OR gene and serum concentrations of oestrogen at the onset of the disease.